ANALISIS LAPORAN KEUANGAN SEBAGAI SALAH SATU ALAT UNTUK MENILAI KINERJA KOPERASI SIMPAN PINJAM (KSP) “SEKAR WANGI” DI CAKRANEGARA - Sri Ayu Febrianti; Saepul Pahmi; Suandi, Suandi (BADAN PENERBIT STIEPARI PRESS, 2021)
This study aims to determine the financial performance so that it can be seen the conditions and achievements that have been achieved by the Savings and Loans Cooperative (KSP)